The Formulasi Dan Uji Aktivitas Antioksidan Sediaan Masker Gel Peel-Off Ekstrak Etanol Daun Kakao (Theobroma cacao L.) - Amelia Arimdani Arifin; Rismayanti Fauziah; Dian Rahmaniar Trisnaputri (CERATA Jurnal Ilmu Farmasi, 2025)
Cocoa leaves (Theobroma cacao L.) are known to have antioxidant activity that can reduce free radicals. There are many preparations on the market that contain antioxidants, one of which is in the form of a peel-off gel mask preparation. The purpose of this study was to formulate a peel-off gel mask preparation from cocoa leaf extract and to determine the phytochemical scent, physical stability and antioxidant activity of the mask preparation using the DPPH method. This study included analytical research. Cocoa leaf extract (Theobroma cacao L.) was prepared by maceration method using 96% ethanol solvent. The peel-off gel mask was formulated with extract percentage of F0 (no extract), FI (10%), FII (15%) and FIII (20%). Antioxidant activity test of peel-off gel mask preparations was carried out at concentrations of 20 ppm, 30 ppm, 40 ppm and 50 ppm. Vitamin C was used as positive control. Absorbance measurements were carried out using a UV-Vis spectrophotometer at a wavelength of 517 nm. The results showed that the preparation of cocoa leaf extract peel-off gel mask fulfilled the requirements of organoleptic test, homogeneity, pH, dry time, viscosity and spreadability. While in the antioxidant activity test, peel-off gel mask preparations at concentrations of 10%, 15% and 20% with the DPPH method have consecutive IC50 values, namely F0 390.351 µg/mL, FI 38.49 µg/mL, FII 31.47 µg/mL and FIII 26.66 µg/mL which are categorised as very strong antioxidants. It is recommended to conduct research on the antibacterial activity of cocoa leaf (Theobroma cacao L.) peel-off gel mask preparations.